Tissue-specific activity of the pro-opiomelanocortin gene promoter. - Jeannotte, L (1987)
The pro-opiomelanocortin (POMC) gene is specifically expressed in corticotroph cells of the anterior pituitary. To define the POMC promoter sequences responsible for tissue-specific expression, we assessed POMC promoter activity by gene transfer into POMC-expressing pituitary tumor cells (AtT-20) and fibroblast L cells. The rat POMC promoter was only efficiently utilized and correctly transcribed in AtT-20 cells. 5'-End deletion analysis revealed two promoter regions required for activity in AtT-20 cells. When tested by fusion to a heterologous promoter, DNA fragments corresponding to both regions exhibited tissue-specific activity, suggesting the presence of at least two tissue-specific DNA sequence elements within the promoter. In summary, POMC promoter sequences from -480 to -34 base pairs appear sufficient to mimic the specificity of anterior pituitary expression.